2018
DOI: 10.1111/lang.12315
|View full text |Cite
|
Sign up to set email alerts
|

Talker and Acoustic Variability in Learning to Produce Nonnative Sounds: Evidence from Articulatory Training

Abstract: Compared to low‐variability training, high‐variability training leads to better learning outcomes and supports generalization of learning. However, it is unclear whether the learning advantage is driven by multiple talkers or by enhanced acoustic variability across target sounds. The current study addressed this issue in nonnative production learning. Spanish speakers were trained to produce the French /e/–/ɛ/ vowel contrast. The stimuli were recorded by five native French talkers for the multiple‐talker (MT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…Results of word stress accuracy showed a general pattern supporting a stronger effect of talker variability for both stress placement and duration measures compared to frequency of exposure. This finding adds to the value of high-variability input for improving L2 pronunciation (Thomson, 2018), revealing that acoustic variability helps enhance pronunciation accuracy not only at the level of segments (e.g., Kartushina & Martin, 2019) but also at the level of individual words. Specifically, regarding stress placement accuracy, the E3 + TV condition produced significantly larger gains than the E3 condition at the immediate posttest.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Results of word stress accuracy showed a general pattern supporting a stronger effect of talker variability for both stress placement and duration measures compared to frequency of exposure. This finding adds to the value of high-variability input for improving L2 pronunciation (Thomson, 2018), revealing that acoustic variability helps enhance pronunciation accuracy not only at the level of segments (e.g., Kartushina & Martin, 2019) but also at the level of individual words. Specifically, regarding stress placement accuracy, the E3 + TV condition produced significantly larger gains than the E3 condition at the immediate posttest.…”
Section: Discussionmentioning
confidence: 59%
“…There were no beneficial effects of a multiple-talker condition (three talkers) over a single-talker condition after completion of two 1-hour perception training sessions over two days. In contrast, Kartushina and Martin (2019) found that Spanish speakers with no experience with French improved production accuracy of the French mid-open and mid-close front unrounded vowels to a greater degree when they listened to the target sounds produced by five talkers than by a single talker. Wiener et al (2020) confirmed the superiority of high-variability training (four talkers) over low-variability training (single talker) for beginner-level L1 English learners studying L1 Mandarin tones after they had received explicit instruction and perception training sessions over four consecutive days.…”
Section: Acoustic Variability and L2 Pronunciation Learningmentioning
confidence: 90%
See 2 more Smart Citations
“…Finally, in order to assess participants' accuracy in the production of novel French vowels, similar to previous studies (Franken et al, 2017;Kartushina et al, 2015Kartushina et al, , 2016Kartushina & Martin, 2019), we computed, in a customised Matlab script, for each vowel token and subject, the Mahalanobis distance (or distance score, DS) between this token and the target acoustic space, de ned as the 20 vowel tokens used for exposure in the familiarization phase. Mahalanobis distance (Mahalanobis, 1936) is a unitless, scale-invariant measure of distance, in terms of standard deviation, from a given point to a distribution, which, by default, takes into account non-circular shape of vowel categories.…”
Section: Reading Taskmentioning
confidence: 99%